The ethics and law of omissions - Nelkin, Dana Kay 1966-; Rickless, Samuel Charles 1964- (Oxford University Press, 2017)
A collection of articles to discuss the moral and legal principles governing omissions. This title addresses questions such as: how we can be morally responsible for things we haven't done, what are the parameters of legal liability when there is nothing identifiable as a criminal act?